Reality and challenges of the work environment of Agricultural Engineers working in the private and non-governmental sectors in the West Bank, Palestine considering some variables - Nassr, Salem Khalil; Zayed, Doaa (Arab Journal for Sciences and Research Publishing, 2023)
This study aimed to identify the reality and challenges of the work environments of agricultural engineers in the non-governmental and private sectors in West Bank, Palestine. The study targeted a sample of 60 agricultural engineers from various disciplines, and from different governorates of the West Bank, working in different jobs within the private and non-governmental sectors. A questionnaire tool was developed and used to collect the responses. The results showed that the average degree of satisfaction with working conditions by the agricultural engineers in the institutions they work in was 3.7 degrees, and it was (average). The results also indicated that the average score for the interest in development and training dimensions for agricultural engineers in the institutions they work in was 2.4 degrees, and its relationship to professional development was (low). The study concluded and recommended that, the most important is developing a protective legal environment for social security and the fairness of its application, as well as emphasizing the importance of various capacity-building programs and their significant impact in shaping accurate and diverse experiences. The results and recommendations of this study will allow employers to listen to the voice of agricultural engineers and their priorities, as well as pay attention to their capacities in achieving results.
Keywords: Agricultural engineer; Private sector; Non-governmental sector; Career development; Agricultural extension